Food Estate for Food Security in Indonesia: An Analysis of Policy Processes, ROCCIPI, and RIA - Frensita Kesuma Twinsani (Faculty of Law, Universitas Sebelas Maret, 2026)
Food security is a fundamental human right and a constitutional obligation of the Indonesian government, yet it still has to deal with long-term structural problems. The Food Estate policy has been pushed as a way for the country to become self-sufficient in food by developing large-scale, integrated agricultural systems. But putting it into action has raised a lot of legal, social, and environmental issues. The objective of this study is to analyse the Food Estate policy through the lens of the public policy process to ascertain the factors contributing to policy failure and deficiencies in regulation design. The study utilises a qualitative methodology, incorporating historical and legal-political perspectives, and is based on statutory approach, and policy documents. The analysis uses Public Policy Stages Theory in conjunction with ROCCIPI and Regulatory Impact Analysis (RIA) frameworks. The study reveals that the Food Estate policy was mostly made from the top down, with little public input, quick environmental assessments, and not enough attention paid to the local socio-ecological conditions. This has led to conflicts over land use and damage to the environment. This findings enhances legal scholarship by emphasising the significance of participatory governance, regulatory impact analysis, and sustainability principles in the development of fair and efficient national food security policy